Removal of Mercury, Antimony, Cadmium and Lead from Aqueous Solution using 1,3,5-Trithiane as an Adsorbent - (:unkn) unknown (SOC BRASILEIRA QUIMICA, 2013)
In this work, 1,3,5-trithiane (TT) was used for removal of Hg(II), Sb(III), Cd(II) and Pb(II) ions from aqueous solutions. The influence of the uptake conditions such as pH, contact time and initial TT feed concentration on the ion binding capacity of TT was tested. Maximum adsorption capacities for Hg(II), Sb(III), Cd(II) and Pb(II) were 35.5 +/- 0.6, 16.9 +/- 0.4, 12.1 +/- 0.1 and 9.5 +/- 0.1 mg g(-1) at pH 5.0, respectively. Selectivity of TT for the ions was determined as having the following decreasing order: Hg(II) > Sb(III) > Cd(II) > Pb(II). Adsorption isotherm models were applied to the experimental data, and the Langmuir model presented as the best fit for the adsorption of Hg(II) ions on TT. Adsorbed toxic metal ions can be effectively desorbed by acid leaching and the regenerated TT can be reused at least five times without any significant loss in adsorption capacity.
Keywords: adsorption; 1,3,5-trithiane; metal-preconcentration; Langmuir model; HEAVY-METAL IONS; FLY-ASH; ADSORPTION; BIOSORPTION; PRECONCENTRATION; SEPARATION; HYDROGEL; RECOVERY; BIOMASS; CD(II)